Consumers evaluations of brand extensions for digital brands - Kut, Deniz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
In this study, consumer attitudes toward extension of the digital brand is investigated along with the effect of intention to adopt extensions of the digital brands. Evaluation of the parent brand (perceived overall quality, perceived trustworthiness, familiarity, favorability and loyalty) attributes, fit of extensions (similarity, capability, require new skills, fits with image, imrpoves brand power and not suprising) attributes and consumer characteristics (Exploratory Tendency in Consumer Behavior, Market Mavenism and Opinion Leadership scales) are claimed to affect consumer attitudes toward digital brand extensions positively. Additionaly type of extensions (conglomerate / concentric) and directions in case of difference examined to has diffirence to indention to adopt digital brand extensions. Four fictional brands are structured one concentric and one conglomerate digital brand extension per each brand; Amazon and Google. These parent brands selected due to being reputable, international brands. Theoretical model and hypotheses are formulated. Three weeks time allocated for an English survey, performed online and 432 valid samples used for the analysis of descriptive, reliability, correlation, one-way ANOVA, paired sample t-tests and multiple regression tests.
Keywords: Branding (Marketing)